Comparison of open vs Plastibell techniques of circumcision for surgical outcomes and cosmetic satisfaction;A randomized control trial - Muhammad Iqbal; Sadaf Ijaz; Muhammad Hassan Zafar; Naveed Akhtar Malik (Journal of Rawalpindi Medical College)
Objective of the study: To compare the results of circumcision by open technique and the Plastibell